2009
DOI: 10.3899/jrheum.081287
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Deficiency and Insufficiency in 2 Independent Cohorts of Patients with Systemic Sclerosis

Abstract: Vitamin D deficiency was very common in the 2 SSc populations, independent of geographic origin and vitamin D supplementation. This suggests that common vitamin D supplementation does not correct the deficiency in SSc patients, and that a higher dose is probably needed, especially in those with high inflammatory activity or severe disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
92
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 88 publications
(100 citation statements)
references
References 40 publications
6
92
1
1
Order By: Relevance
“…Auto-antibodies profile, including anti-topoisomerase antibody I (Scl 70), anti-nuclear antibodies (ANA) and anti-centromere antibodies (ACA), has been reported to be associated with low hormone levels by Vacca et al, but following reports in the same findings failed [9][10][11]; [13][14][15][16][17]. Lately, Carmel et al reported no correlation between antivitamin D antibodies and some clinical features [18].…”
Section: Discussionmentioning
confidence: 93%
See 4 more Smart Citations
“…Auto-antibodies profile, including anti-topoisomerase antibody I (Scl 70), anti-nuclear antibodies (ANA) and anti-centromere antibodies (ACA), has been reported to be associated with low hormone levels by Vacca et al, but following reports in the same findings failed [9][10][11]; [13][14][15][16][17]. Lately, Carmel et al reported no correlation between antivitamin D antibodies and some clinical features [18].…”
Section: Discussionmentioning
confidence: 93%
“…Although Arnson et al enrolled the most large patients group, demographic and clinical data was incomplete [10]. Other limitations due to mixed participants (Italian and French) were presented by Vacca et al [14].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations